PERAN NARASI KOMUNIKASI TERAPEUTIK KONSELOR PADA PASIEN PECANDU NARKOBA DI BADAN NARKOTIKA NASIONAL PROVINSI JAWA TIMUR - Marcella Nethania Thessalonika (Universitas 17 Agustus 1945 Surabaya, 2026)
Drug abuse is a significant issue and negatively impacts health and social life. The high number of drug cases in East Java Province demonstrates the need for comprehensive and sustainable treatment. This study examines how counselors use therapeutic communication with drug addicts at the East Java National Narcotics Agency (BNN). This study employed descriptive qualitative research, employing observation, indepth interviews, and documentation as data collection techniques. Subjects included addiction counselors and drug educators at the East Java BNN. Narrative Theory and Health, along with a fear appeals approach, were used to understand the narratives used in counseling. The results indicate that effective therapeutic communication by counselors encompasses the counseling stages of exploring feelings during pre-interaction, self-acceptance, and providing reinforcement and affirmation during the work phase. Counselors use narratives in counseling, which play a role in building awareness, strengthening selfcontrol, and changing the behavior of drug addicts during their recovery process. Therapeutic communication narratives play a crucial role in supporting the rehabilitation process of drug addicts at the East Java National Narcotics Agency (BNN). Warm interpersonal relationships, empathy, and sincerity from the counselor can be key to successful rehabilitation. The use of narratives in therapeutic communication has been shown to contribute to creating meaning, increasing awareness, and encouraging behavioral changes in drug addicts during rehabilitation. This study concludes that therapeutic narratives play a role in supporting the successful rehabilitation of drug addicts. This study is also expected to provide theoretical and practical contributions to the development of therapeutic communication and to improving the quality of drug addict rehabilitation services through professional and humanistic therapeutic communication.Keywords: Therapeutic Communication, Counselor, Drug Addict, Rehabilitation, East Java National Narcotics Agency